Analysis Of Work Posture Using The Rapid Office Strain Assessment (ROSA) And Rapid Upper Limb Assessment (RULA) Methods In Office Administration Employees - Miranti Dewi Sartika Nurul Fajria; Elly Ismiyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
In the modern era, the use of computers has become the main tool in office activities. Employees who spend long periods of time in a sitting position and operating a computer are at risk of various health problems, especially when they do not pay attention to ergonomic aspects while working. Even though ergonomic risks can affect employee health and productivity in the long run. The results of the initial identification with the distribution of the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) questionnaire to office administration employees at PT Karya Sidorukun Santosa showed that they experienced complaints such as pain in the head, neck tension, back pain, and difficulty concentrating. This study was conducted to analyze ergonomics risks in office administration employees at PT Karya Sidorukun Santosa using the Rapid Upper Limb Assessment (RULA) and Rapid Office Strain Assessment (ROSA) methods. The results of the RULA analysis showed that 50% of employees needed further investigation with a score of 4, 33.3% needed immediate change with a score of 5, and 16.7% needed immediate action with a score of 7. The ROSA score ranged from 4 to 7, indicating the need to upgrade facilities and workspace layouts to reduce the risk of musculoskeletal disorders. These improvements are important to improve the comfort and productivity of administrative employees. Keywords: Ergonomics, RULA, ROSA, Administrative Employees.